Prevalence and Incidence of Childhood Arterial Ischaemic Stroke and Haemorrhagic Stroke in China: Results of Post Hoc Subgroup Analysis From a Nationally Representative Cross-Sectional Survey. - Jiang, Bin; Sun, Haixin; Ru, Xiaojuan; Sun, Dongling; Ge, Siqi; Wang, Wenzhi (Journal of Central Nervous System Disease, 2025)
Background and purpose: Nationwide data on childhood stroke prevalence and incidence in Mainland China are unavailable now. We aim to investigate the prevalence and incidence of childhood arterial ischaemic stroke and haemorrhagic stroke in China nationwide. Methods: In 2013, we implemented a nationally representative, door-to-door epidemiological survey on stroke in China through a complex, multistage, probability sampling design. A post-hoc subgroup analysis was conducted to examine both the crude point prevalence and annual incidence of childhood stroke. Due to the small case number, the Poisson distribution was used to estimate the 95% confidence intervals (CIs) for the crude rates. Results: In this survey, only 4 strokes were identified. The crude point prevalence of childhood stroke was 4.82 (95% CI: 1.31-12.34) per 100 000 children in China; 4.51 (95% CI: 0.55-16.29) per 100 000 boys, and 5.17 (95% CI: 0.63-18.69) per 100 000 girls. Haemorrhagic stroke prevalence was 3.61 (95% CI: 0.75-10.56) vs 1.20 (95% CI: 0.03-6.71) per 100 000 children for arterial ischaemic stroke. The crude annual incidence of childhood stroke was 2.34 (95% CI: 0.28-8.45) per 100 000 children in China; 5.01 (95% CI: 0.60-18.10) per 100 000 girls. The crude annual incidences of both arterial ischaemic stroke and intracerebral haemorrhage were the same at 1.17 (95% CI: 0.03-6.52) per 100 000 children. Conclusions: The point prevalence and annual incidence estimates of childhood stroke were 4.82 and 2.34 per 100 000 children in China, respectively. Chinese children may have more prevalent cases of haemorrhagic than arterial ischaemic strokes.